Chemical selectivity in electrochemical surface oxidation enhanced Raman scattering. (1st September 2020) - Perez-Estebanez, Martin; Hernandez, Sheila; Perales-Rondon, Juan V.; Gomez, Elvira; Heras, Aranzazu; Colina, Alvaro
Abstract: Electrochemical Surface Oxidation Enhanced Raman Scattering (EC-SOERS) is an interesting and promising phenomenon capable of amplifying the Raman signal in a similar way to Surface Enhanced Raman Scattering (SERS), but EC-SOERS takes place during the oxidation of a silver substrate. This phenomenon was originally described for specific electrolytic conditions in which a small amount of chloride in acidic medium was mandatory to obtain a substantial enhancement. Herein, we demonstrate that EC-SOERS can be also observed in presence of KBr, showing a potential-dependent behavior. Moreover, in this work a novel approach to reach chemical selectivity during time resolved Raman spectroelectrochemistry (TR-Raman-SEC) experiments is proposed. This new approach is based on the effect of the electrolytic medium on the structures that are formed on the electrode surface. SEM studies were carried out to study the origin of this selectivity. Although SEM images reveal clear differences between the structures of silver halides formed on the electrode surface during the oxidation of the substrate, the absence of EC-SOERS effect at open circuit potential hinders the identification of the actual structures responsible for the phenomenon. Graphical abstract: Image 1 Highlights: EC-SOERS has been observed in KBr medium for the first time. EC-SOERS can provide chemical selectivity by tailoring of the electrolytic medium. EC-SOERS is observed for carboxylic acids and aromatic rings with carbonyl groups. EC-SOERS has to involve some kind of electromagnetic effect.